Psychotropic drugs use in young university students (Research, Society and Development, 2021)
Psychic illness in university students and psychotropic drugs use in this population has gained prominence in current studies. Common mental disorders diagnoses such as anxiety and depression are found in most students, and when untreated, these symptoms can lead to greater harm. Therefore, this study aimed to carry out the last five years bibliographic studies related to the use of psychotropic drugs in higher education. The search was carried out in CAPES, Scielo and Google Academic databases, using the keywords: psychopharmaceuticals; academics; drugstore; student health and prevalence. Ten studies were selected among articles, theses and dissertations. It was observed that the prevalence of mental illness is in females. A large part of this public uses antidepressant, calming and stimulant medications to treat depressive symptoms, anxiety, difficulty in sleeping and to increase academic performance. Many students use it on the recommendation of friends or third parties without a prescription. Daily stress, academic demands, reconciling work, study and unfavorable socioeconomic conditions contribute to mental illness.